The mother-daughter relationship in eating disorders: the psychotherapy group of mothers - Cobelo,Alicia Weisz (2012)
Psychotherapeutic interventions that bring about differentiation, separation, individuation and autonomy in the mother-daughter relationship are recommended as treatment for eating disorders. With this goal in mind, a psychotherapy group for mothers was organized in an outpatient program for adolescents with eating disorders at a public institution, as one of the psychotherapeutic approaches in the multidisciplinary treatment of adolescent patients. Evidence suggests that this approach can be relevant and effective in the treatment of eating disorders.